ELF feito no Brasil: reflecting glocally about knowledge validity in the epistemic Global South - Fiorese, John (Árboles y Rizomas, 2025)
This article aims to explore the concept of English as a Lingua Franca (ELF) feito no Brasil, critically reflecting on knowledge production and the criteria that determine what is considered valid knowledge. By analyzing ELF feito no Brasil as an epistemic stance, this paper seeks to challenge Eurocentric knowledge production and explore alternative epistemic positions that arise from the Global South. Through a glocal lens based on decolonial ideas, the paper highlights how local and global dynamics intersect, questioning dominant paradigms and advocating for more inclusive and diverse approaches to knowledge validation concerning the English language. This reflection not only broadens the understanding of ELF in other parts of the world, but also contributes to the broader endeavor of decolonizing knowledge from the epistemic Global South.
Keywords: ELF feito no Brasil; knowledge validity; epistemic Global South; glocal perspective; decolonizing knowledge